If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2x = 4x + -4 Combine like terms: 3x + 2x = 5x 5x = 4x + -4 Reorder the terms: 5x = -4 + 4x Solving 5x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = -4 + 4x + -4x Combine like terms: 5x + -4x = 1x 1x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 1x = -4 + 0 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 30=k+18 | | 4+3n-77=0 | | 208x=-4 | | 36x^2-4y^2=0 | | 2c-1=1 | | 2ln(5x)-ln(2x)=2.5 | | a-5=21 | | 5(d-15)=90 | | -8x=x^2+15 | | 8a+4-7a=3 | | p+6=28 | | y=3x^4-4X^3-12 | | 1.6r=80 | | 3.5h=x | | 4x-17=-2x+25 | | 26+t=27 | | -5(x-2)+6x=9-8 | | 2x+5x=5x+9x | | c^2-16c=0 | | X(y^7-6)+6(y^7-6)=0 | | 2(2n+1)= | | 6(1.3p-3)=2.p-5 | | -4(x-2)+5x=5-6 | | 3(x-2)=2(x+6) | | ln(6x+1)= | | -(36)=-0.025c | | (a-b)2-(a+b)2= | | t-5=19 | | 9a-5-8a=-3+2 | | 7(p+1)-13(p-2)=2(p-3)+11 | | 0.2=5y | | 5n-2=2n-14 |